Code Switching in English Classroom Interaction at Grade VIII of SMPN 27 Medan - Mira Mailani; Murni Murni; Nayla Firzanah; Stefani Angelica (Komprehensif, 2026)
This study aimed to analyze the types of code-switching used by the English teacher and the reasons for using code-switching during classroom interaction at Grade VIII of SMPN 27 Medan. This study employed a descriptive qualitative research design. The data were collected through classroom observation, audio recording, and semi-structured interviews during the teaching and learning process. The collected data were analyzed using Miles, Huberman, and Saldaña’s qualitative data analysis model consisting of data condensation, data display, and conclusion drawing. The findings revealed that the teacher used three types of code-switching based on Poplack’s theory (1980), namely intra-sentential switching, inter-sentential switching, and tag switching. Among those types, intra-sentential switching became the dominant type because the teacher frequently mixed English and Indonesian within the same utterance while explaining materials and giving classroom instructions. Furthermore, the findings showed that the teacher used code-switching for several communicative reasons based on Gumperz’s theory (1982), namely message qualification, personalization versus objectification, and addressee specification. Message qualification became the dominant reason because the teacher frequently switched to Indonesian to clarify explanations and facilitate students’ understanding during the learning process. The findings indicate that code-switching plays an important role in supporting effective classroom communication, improving students’ comprehension, reducing students’ anxiety, and creating a comfortable learning atmosphere in EFL classrooms. Therefore, code-switching can be considered an effective pedagogical strategy in English language teaching, especially in junior high school classrooms where students still have limited English proficiency.